2023
DOI: 10.1080/07853890.2023.2206672
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of tracheal, bronchus, and lung cancer attributable to occupational carcinogens in 204 countries and territories, from 1990 to 2019: results from the global burden of disease study 2019

Abstract: Background Occupational-related cancers are a substantial global health issue. The largest proportion of occupational-related cancers is tracheal, bronchus, and lung (TBL) cancer. This study aimed to explore the geographical and temporal trends in occupational carcinogens related to TBL cancer. Methods Data on TBL cancer attributable to occupational carcinogens were collected from the Global Burden of Disease Study 2019. Numbers and age-standardized rates (ASRs) of deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…210,211 From 1990 to 2019, the trends of ASRs of deaths and DALYs in lung cancer due to occupational burden decreased globally; however, they increased in low, lowmiddle and middle SDI regions, and in females. 212 The top three causes were attributed to occupational exposure to asbestos, silica and diesel exhaust. The ASRs of deaths and DALYs of occupational asbestos and silica exposure decreased worldwide outside of lower SDI regions, whereas those of diesel exhaust exposure increased globally.…”
Section: Malignant Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…210,211 From 1990 to 2019, the trends of ASRs of deaths and DALYs in lung cancer due to occupational burden decreased globally; however, they increased in low, lowmiddle and middle SDI regions, and in females. 212 The top three causes were attributed to occupational exposure to asbestos, silica and diesel exhaust. The ASRs of deaths and DALYs of occupational asbestos and silica exposure decreased worldwide outside of lower SDI regions, whereas those of diesel exhaust exposure increased globally.…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…The ASRs of deaths and DALYs of occupational asbestos and silica exposure decreased worldwide outside of lower SDI regions, whereas those of diesel exhaust exposure increased globally. 212 The risk of lung cancer is attributed to cumulative asbestos exposure and does not require the development of asbestosis, 213 and the risk of lung cancer multiplicatively increases in people with both asbestos exposure and smoking. Asbestos exposure increases the risk of lung cancer, even in never smokers.…”
Section: Malignant Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have reported associations between long-term exposure to certain heavy metals and the development of cancers, cardiovascular diseases, neurodevelopmental disorders, and adverse reproductive outcomes. Nevertheless, there is a scarcity of studies that specifically address Iranian provinces, despite the distinctive environmental and socio-economic factors in the country that could potentially affect the presence of heavy metals in drinking water sources 18 , 19 . By conducting this evaluation in different parts of Iran, we can contribute valuable insights to the limited body of knowledge on heavy metal exposure and its health consequences in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Cd can induce lung cancer, which has already been widely recognized through numerous research studies. Numerous reports have found that cadmium inhalation leads to respiratory cancers including tracheal cancer, bronchus cancer and lung cancer [ 9 - 11 ]. Additionally, occupational exposure to Cd is known to have adverse effects on the prostate [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%